Optical Mapping of Plasmodium falciparum Chromosome 2 - Jing, Junping; Lai, Zhongwu; Aston, Christopher; Lin, Jieyi; Carucci, Daniel J.; Gardner, Malcolm J.; Mishra, Bud; Anantharaman, Thomas S.; Tettelin, Hervé; Cummings, Leda M.; Hoffman, Stephen L.; Venter, J. Craig; et al. (Genome Research, 1999)
Detailed restriction maps of microbial genomes are a valuable resource in genome sequencing studies but are toilsome to construct by contig construction of maps derived from cloned DNA. Analysis of genomic DNA enables large stretches of the genome to be mapped and circumvents library construction and associated cloning artifacts. We used pulsed-field gel electrophoresis purified Plasmodium falciparum chromosome 2 DNA as the starting material for optical mapping, a system for making ordered restriction maps from ensembles of individual DNA molecules. DNA molecules were bound to derivatized glass surfaces, cleaved with NheI or BamHI, and imaged by digital fluorescence microscopy. Large pieces of the chromosome containing ordered DNA restriction fragments were mapped. Maps were assembled from 50 molecules producing an average contig depth of 15 molecules and high-resolution restriction maps covering the entire chromosome. Chromosome 2 was found to be 976 kb by optical mapping withNheI, and 946 kb with BamHI, which compares closely to the published size of 947 kb from large-scale sequencing. The maps were used to further verify assemblies from the plasmid library used for sequencing. Maps generated in silico from the sequence data were compared to the optical mapping data, and good correspondence was found. Such high-resolution restriction maps may become an indispensable resource for large-scale genome sequencing projects.